Real‐life efficacy and safety of secukinumab in elderly patients with psoriasis over a 2‐year period. (2nd June 2020) - Megna, M.; Camela, E.; Cinelli, E.; Fabbrocini, G.
Abstract: Background: The prevalence of psoriasis is increasing among older people. Elderly patients with psoriasis represent a challenge for dermatologists owing to multiple comorbidities, polypharmacy and immune senescence, which lead to an increased possibility of adverse events (AEs), drug interactions and susceptibility to cancers and infections. Therefore, conventional systemic therapies are often contraindicated, with biologics appearing as the mainstay for moderate‐to‐severe disease. However, the data on efficacy and safety of biologics in older people are scant. Aim: To evaluate the efficacy and safety of secukinumab in elderly patients with psoriasis over a 2‐year period. Methods: A real‐life retrospective observational study was performed on patients aged ≥ 65 years with moderate‐to‐severe plaque psoriasis who were treated with secukinumab at the Psoriasis Care Unit of the University of Naples Federico II, Italy from June 2016 to June 2019. Results: Mean Psoriasis Area Severity Index (PASI) reduced from 11.4 ± 6.3 at baseline to 2.1 ± 1.7 at week 24 and 1.7 ± 1.9 at week 96 ( P  < 0.001 for all follow‐up visits), with a final mean PASI reduction of 85.1%. A similar trend was noted for body surface area (BSA), with baseline value of 27.5 ± 15.7 decreasing to 6.8 ± 5.0 at week 24, and to 3.3 ± 2.5 at week 96 ( P  < 0.001 at all follow‐up visits), with a final mean BSA score reduction of 88.0%. Registered AEs did not lead to secukinumab discontinuation, except in one patient (3.4%). Conclusion: Secukinumab seems to be a safe and effective treatment for elderly patients with psoriasis, who frequently have multiple comorbidities, polypharmacy and multiple failures with previous systemic treatments including biologics.